Psychiatric and neurocognitive disorders among HIV-positive and negative veterans in care: Veterans Aging Cohort Five-Site Study. - Justice, Amy C; McGinnis, Kathleen A; Atkinson, J Hampton; Heaton, Robert K; Young, Corinna; Sadek, Joseph; Madenwald, Tamra; Becker, James T; Conigliaro, Joseph; Brown, Sheldon T; Rimland, David; Crystal, Steve; et al. (AIDS (London, England), 2004)
The risk for psychiatric and neurocognitive disorders among middle-aged and older individuals with HIV infection has not been well characterized.
Keywords: Adult; Age Distribution; Aged; Aged, 80 and over; Aging; Alcohol Drinking; Cognition Disorders; Cohort Studies; Depressive Disorder; Female; HIV Seronegativity; HIV Seropositivity; Humans; Male; Memory Disorders; Mental Disorders; Middle Aged; Neuropsychological Tests; Prevalence; Substance-Related Disorders